Implementasi Peningkatan Kualitas Pelayan Terhadap Kepuasan Pelanggan Menggunakan Metode SWOT di Altha Hotel - Merlia Rahmayani (Politeknik Kampar, 2022)
In today's global era, there is intense competition in the business world, especially companies in the hospitality service sector. Hotel is a company that is managed by the owner by providing services. In the midst of today's global competition, it is important for every hotel employee to improve services in order to compete with other hotels. The quality of services and facilities at this time is more important in the business world because it is thought to have an effect on customer satisfaction, and will also take into account the competition arising from various hospitality services. The facilities used by each company are of various forms, types and benefits. The purpose of this study was to analyze the effect of service quality on customer satisfaction at Altha Hotel. The population is people who have the potential to go to hotels where the economy is middle and above. The research sample was 98 respondents. This research uses the SWOT method.